Employment law - Beryl Grant (Thomson Learning, 2002)
Students of Human Resource Management and professional managers often find the legal aspect of their study or work overly complex. This comprehensive text provides an invaluable resource to these groups, by offering an accessible explanation of employment law to non-lawyers. 'A valuable resource for non-specialist students and managers' Dr Nick Bacon, University of Nottingham Business School 'A knowledgeable and useful book on what is a complex and growing aspect of the manager's world. It has a more 'lively' feel to it than many of the standard texts on employment law' Martin Dowling, Dundee Business School, University of Abertay Ideal for undergraduate business and management students focusing on HRM and postgraduate students on specialist HRM, CIPD and MBA courses this accessible text also provides a comprehensive and succinct introduction to all the key aspects for any professional manager dealing with employee issues